c - Paul, Ann Whitford (New York : Scholastic Inc, 2004)
Iguana, Conejo, Tortuga and Culebra are excited about having a spring party, but only Iguana is willing to do any of the work. Includes a glossary of spanish words used.
Keywords: Iguanas -- Fiction; Desert Animals -- Fiction